Pengaruh Sikap, Personal Cost Of Reporting, Dan Tingkat Keseriusan Kecurangan Terhadap Intention Whistleblowing Pada Pemerintah Daerah - Hutriyal Alwi; Nayang Helmayunita (Universitas Negeri Padang, 2020)
This study aims to determine: the extent of the influence of attitude variables, the personal cost of reporting on fraud disclosure decisions or whistleblowing intention. The sample selection in this study uses a purposive sampling method in which the respondents are the ASN working in the Local Government Organizations (OPD) in Padang Pariaman. Respondents consisted of 104 people, who served at the head of the finance department, treasurer of the expenditure department, treasurer of the procurement of goods, as well as staff in the financial and accounting departments. Data collection techniques used in this study were using a questionnaire. Questionnaires that have been collected and filled out in full will be processed by data. From the results of data processing, it can be seen that the attitude variable has no effect on whistleblowing intention with a count of 1.477 <t table 1.983, it can be said that the first hypothesis was rejected. While the results of the personal cost of reporting testing are also known to affect whistleblowing intention with a count of 6.407> 1.983 tables. But the hypothesis was rejected due to a positive effect. For the Level Intention of Fraud variable, it is known that it has a significant positive effect with count 2,280> t table 1,983. So that it can be said that the third hypothesis is accepted.